Evolution of larval characteres in Dendrobatoidea Cope, 1865 (Amphibia; Anura; Dendrobatidae & Aromobatidae) - Dias, Pedro Henrique dos Santos (2018)
Tadpoles represent a key element in evolutionary history and the diversification of anurans. Through a two-phase life cycle, anurans can take advantage of the available resources in terrestrial and aquatic environments. Several studies have demonstrated that larval morphology may represent an important source of evidence for evolutionary studies. However, tadpoles are often ignored and little is known about their anatomy and biology. An example of this problem is the superfamily Dendrobatoidea, for which there is almost no information on tadpoles. This study aims to fill this gap. I performed a cladistic analysis of the superfamily Dendrobatoidae with emphasis on larval characters. The final dataset also included adult phenotypic characters and DNA sequences. The final matrix was composed of 621 terminals and more than 500 phenotypic characters of which 392 were individualized from larval systems, such as chondrocranium, cranial musculature and buccopharungeal anatomy. In my optimum hypothesis I recovered Dendrobatoidea as well as all its subfamilies and genera as monophyletic. Larval characters optimized as synapomorphies at different levels. Based on the topology and distribution of the characters, I discuss the evolution of several lifestyles and morphologies, such as oophagy, endotrophy, and carnivory in Dendrobatoidea